The Role of Philosophical Hermeneutics in Contextual Qur’anic Exegesis in the Digital Age (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
This research aims to analyze the role of philosophical hermeneutics as a methodological framework in shaping contextual Quranic exegesis in the digital age. The focus of this study is to address the challenges of disinformation and the fragmentation of religious understanding rampant in cyberspace. Using a qualitative approach with a library research method, data was collected from primary and secondary literature, then analyzed using a content analysis technique with a hermeneutic perspective. The findings indicate that philosophical hermeneutics, with its core concepts like "fusion of horizons" and "historical consciousness," is crucial for bridging the sacred text with contemporary reality without sacrificing its authenticity. The study also produced a pragmatic implementation model consisting of four stages for navigating the complexities of exegesis in the digital era. The implication of this research is a shift in the authority of exegesis from a dogmatic to a dialogical model, which fosters a more wise, responsible, and adaptive understanding of the Quran to the dynamics of the times.